2023
DOI: 10.3390/f14101992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microbial Decay and Microbial Communities in Waterlogged Archaeological Rosewood (Dalbergia Species)

Jong Sik Kim,
Minseok Kim,
Ju Won Lim
et al.

Abstract: While numerous studies have examined microbial attacks on waterlogged archaeological wood, limited information is available regarding microbial attacks in waterlogged tropical hardwoods submerged in marine environments. In this context, we explored microbial attacks in waterlogged archaeological rosewood (Dalbergia species), a tropical hardwood species that was submerged in the Yellow Sea for approximately 700 years, using various microscopic techniques and next-generation sequencing (NGS) methods. Based on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 57 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…With respect to relevance to the longevity of ancient waterlogged woods, the contribution of tension wood is expected to be insignificant, as the presence of a G-layer is considered to render tension wood fibres more susceptible to wood-destroying fungi than normal wood fibres [13]. However, in a recent study of the microbial decay in waterlogged archaeological rosewood, Kim et al [31] found the G-layer in tension wood fibres to show some resistance in the initial stages of attack by soft-rot fungi. From a biotechnological perspective, the unique features of tension wood fibres, particularly the presence of the cellulose-rich G-layer, are being exploited in developing processes to enhance bioethanol production from woody biomass rich in tension wood.…”
Section: Tension Wood Cell Wallsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to relevance to the longevity of ancient waterlogged woods, the contribution of tension wood is expected to be insignificant, as the presence of a G-layer is considered to render tension wood fibres more susceptible to wood-destroying fungi than normal wood fibres [13]. However, in a recent study of the microbial decay in waterlogged archaeological rosewood, Kim et al [31] found the G-layer in tension wood fibres to show some resistance in the initial stages of attack by soft-rot fungi. From a biotechnological perspective, the unique features of tension wood fibres, particularly the presence of the cellulose-rich G-layer, are being exploited in developing processes to enhance bioethanol production from woody biomass rich in tension wood.…”
Section: Tension Wood Cell Wallsmentioning
confidence: 99%
“…For waterlogged woods, recent microscopic studies have provided evidence of cell wall degradation by cavity-producing soft-rot fungi (Type I), tunnelling bacteria, and erosion bacteria, or predominantly by erosion bacteria [6,9,[15][16][17]27,[29][30][31]. Cell wall erosion-type attacks by soft-rot fungi (Type II) were rarely observed in such woods [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their excellent compressive strength provides them with outstanding internal bonding strength when used as adhesives, and the rod-like 5-phase crystals formed during hydration can be well anchored to the porous surface of wood, using the vessel channels and pits as the potential anchor points for the 5-phase crystals. 8,9 Therefore, MOC composites have natural advantages as wood adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, aldehyde-containing adhesives still occupy the main position in the wood adhesives industry. , Formaldehyde-containing adhesives inevitably release harmful gases such as formaldehyde during production and use, which threatens the balance of the ecological environment and endangers human health. Inorganic adhesives work over a wider temperature range and do not release volatile organic compounds during use, making them more environmentally friendly. , Magnesium oxychloride cement (MOC) composites are a new type of inorganic cementitious material that do not release harmful gases during preparation and use. Their excellent compressive strength provides them with outstanding internal bonding strength when used as adhesives, and the rod-like 5-phase crystals formed during hydration can be well anchored to the porous surface of wood, using the vessel channels and pits as the potential anchor points for the 5-phase crystals. , Therefore, MOC composites have natural advantages as wood adhesives.…”
Section: Introductionmentioning
confidence: 99%